INTEGRATION OF SOCIO-CULTURAL EDUCATION VALUES IN INDONESIAN LANGUAGE LEARNING FOR ELEMENTARY SCHOOL STUDENTS - Muh. Safar (International Journal of Teaching and Learning, 2024)
One way used to introduce local cultural values to the younger generation is through learning at school. Learning in schools needs to take a role that can optimize the inheritance of cultural values to the young generation of Indonesia, so that the young generation knows and has a sense of belonging to their national culture and integrates it in their lives to form their unique identity as a dignified Indonesian nation. The shift in language culture which is increasingly decreasing in society is a serious problem that must be addressed. This shift is the widespread use of harsh language in community interaction activities. What is even more worrying is that people consider it a normal and normal thing to use. This is the basis for integrating various educational values in PBI learning to create an academic society that is polite and intelligent in language. Examples in the language sub-discussion relate to society and culture. The discussion can be directed to PSB values in the form of social and cultural values, meaning that the language process is part of the culture of a community. It is not limited to this, but explains that language can represent a person's culture and vice versa, community culture can be seen from the community's language patterns.